Diagnosis and Molecular Marker Analysis of Bali’s Rabies Virus Isolates (DIAGNOSIS DAN ANALISIS PENANDA MOLEKULER VIRUS RABIES ISOLAT BALI) - Dibia, I Nyoman; Sumiarto, Bambang; Susetya, Heru; Putra, Anak Agung Gde; Mahardika, I Gusti Ngurah Kade; Scott-Orr, Helen (Jurnal Veteriner; Vol 15 No 3 (2014), 2014)
The direct fluorescent antibody test (dFAT) was recommended by both World Health Organization(WHO) and Office International des Epizooties (OIE) as a standard diagnostic technique for rabies. Sincethe outbreak of rabies in Bali, it was ascertain the importance to develop a reverse transcriptase-polymerasechain reaction (RT-PCR) technique with specific primers as an alternative diagnostic method. The aim ofthis study was to develop a RT-PCR technique for rabies diagnosis in animals and find out the molecularmarker of Bali’s rabies virus (BRV) isolates based on the sequence of nucleoprotein (N) gene. Brainsamples were obtained during 2009 from 14 suspected rabid dogs and one cattle, where rabies viruseswere isolated. The dFAT was used to detect the presence of rabies viral antigen. Ribonucleic acid (RNA) ofrabies viruses was extracted with TRIzol reagent. Fragment of N gene was amplified using one-step RTPCRmethod with specifically-designed primer pairs and sequenced using ABI automatic sequencer. Multiplealignment of nucleotide and deduced amino acid sequences were analyzed using ClustalW of MEGA 4.0program. This study found that twelve out of fifteen animal brain samples confirmed as rabies by dFAT.Similarly, a single band of 1215 bp PCR product for rabies virus was also detected in twelve out of twelve(100%) dFAT rabies positive samples. It is therefore evident that alternative diagnostic of rabies inanimals can be established using RT-PCR technique. The results showed that the RT-PCR has a very highagreement with dFAT. Polymorphic sites of N gene of twelve BRV isolates were identified at the position186, 501, 801, 840, 1068 and 1153. Bali’s rabies virus isolates have conserved amino acid (isoleucine)alterations at position 308 (open reading frame). Isoleucine distinguished between all Bali’s isolates andthe all of isolates from other area of Indonesia and other part of the world. This finding significantlydifferent as compared to other rabies virus isolates from other part of Indonesia or the world documentedon the GenBank. Accordingly it is proposed that it can be used as molecular marker and believed to be thefirst study of molecular marker of rabies virus in Indonesia.
Keywords: rabies virus, diagnosis, molecular marker, nucleoprotein gene, Bali